The Global Bookshelf for Children: An Interdisciplinary Approach to Promoting Literacy and Education for the Global Village - Rankin, Carolynn; Swiniarski, Louise Boyle; Brock, Avril (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The aim of the project is to develop a global education model for The Global Bookshelf for children based on early childhood pedagogy and collection development and management principles from library and information science. Using an action research approach the researchers will compare use of The Global Bookshelf by practitioners in… Le but de ce projet est de mettre en place un modèle éducatif pour la Bibliothèque Globale destinée aux enfants et basé sur la pédagogie des jeunes enfants, sur le développement des collections, et sur les principes de gestion de la bibliothèque et des sciences de l’information. En utilisant une approche de recherche-action, les chercheurs comparent l’utilisation de la Bibliothèque Globale par…